Current Ratio, Debt to Equity Ratio, Total Asset Turnover, Return on Asset, Price to Book Value sebagai Faktor Penentu Return Saham (Management Analysis Journal, 2014)
The purpose ofthis studyistoexamineandanalyze thefinancial ratio is measuredwithCurrent Ratio, Debt to Equity Ratio, Total Asset Turnover, Return On Asset, Price to Book Value towards share return. The populationin this study areallReal Estate and Property Industri Listed inthe indonesia stock exchange since period 2012-2013, with the total of47companys. Thestudysamplewas takenby purposive sampling method, with the total of 31company. This study usesdata analysisof multiple linear regression analysis to estimated of dependent variable’s value from independent variable’s. Based onthe research results, it can be known that only price to book value has a significant effect toward share return and for current ratio, debt to equity ratio, total asset turnover, return on asset has not a significant effect toward share return.